2014
DOI: 10.1097/mlr.0b013e3182a51b3d
|View full text |Cite
|
Sign up to set email alerts
|

Out of Context

Abstract: Extant clinical practice guidelines for one chronic disease sometimes consider the context of the patient with that disease, but only do so narrowly. Guideline panels must remove their contextual blinders if they want to practically guide the care of patients with MCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 6 publications
1
48
0
Order By: Relevance
“…While we found that the timing of the measurements relative to the baseline and 6-month benchmarks varied considerably and fell outside a 1–2-week window for some clients, this was due in part to the use of existing client records to obtain these measures (e.g., participants did not provide bloodwork specifically for this study). The overriding concern with this measure was the evidence indicating its poor connection with patient-relevant issues [26]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While we found that the timing of the measurements relative to the baseline and 6-month benchmarks varied considerably and fell outside a 1–2-week window for some clients, this was due in part to the use of existing client records to obtain these measures (e.g., participants did not provide bloodwork specifically for this study). The overriding concern with this measure was the evidence indicating its poor connection with patient-relevant issues [26]. …”
Section: Resultsmentioning
confidence: 99%
“…This measure appeared more promising, in that participants in our study did not experience difficulty interpreting the SF-12 questions, the summary scores generated from the SF-12 instrument (PCS and MCS) represent well-validated measures of HRQoL, published norms exist for comparison with the Canadian general population, and the PCS score captures physical functional ability which appears to be an important outcome for patients [26]. A recent systematic review found that the PCS was frequently used as a primary outcome in the evaluation of interventions similar to ours for adults with chronic or long-term health conditions [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Key in all of these approaches is optimising care by carefully tailoring treatment to the context and preferences of the individual (older) patient with multimorbidity. However, systematic reviews suggest that these principles are generally poorly applied in guidelines for this group [2528]. One review looked at primary CVD prevention in older people specifically, and showed that only a handful of clinical practice guidelines adequately addressed evidence about potential benefits and harms of CVD prevention in older people or how to tailor CVD management to multimorbidity and limited life expectancy [25].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] These patterns may be due to broadened definitions of disease, misapplied diagnostic criteria, defensive medicine, blindness to comorbid and social contexts, or inaccurate estimation of harms and benefits by clinicians or patients. 13,[15][16][17][18] Personalised or precision medicine paradigms, depending on their application, may further this trend by driving additional diagnostic or genomic testing in the search for targeted treatments.…”
Section: Overmedicalisationmentioning
confidence: 99%